Evaluating the Impact of Technology Investments on Economic Performance and Operational Efficiency in Diverse Industry Sectors - Adelfrini, Nadhila; Syamsurianti, Syamsurianti; Shanaya, Shanty (Scieclouds Publishing, 2023)
This study explores the impact of strategic resource allocation on economic management excellence, focusing on profitability, return on investment (ROI), operational efficiency, and market share growth. Utilizing quantitative methods, including ANOVA and regression analysis, the research examines how varying levels of financial, technological, and human resource deployment influence these performance metrics across different industry sectors. The results reveal significant variations in economic outcomes based on resource allocation, highlighting the importance of tailored strategies for optimal performance. This study addresses gaps in the literature by providing empirical evidence of the direct effects of resource allocation on organizational success and offers insights for refining resource management practices.